Differences in δ- and μ-Opioid Receptor Blockade Measured by Positron Emission Tomography in Naltrexone-Treated Recently Abstinent Alcohol-Dependent Subjects - Weerts, Elise M; Kim, Yu Kyeong; Wand, Gary S; Dannals, Robert F; Lee, Jae Sung; Frost, J James; McCaul, Mary E (Neuropsychopharmacology (New York, N.Y.), 2008)
Blockade of brain μ -opioid receptor ( μ -OR) and δ -opioid receptor ( δ -OR) was investigated in recently abstinent alcohol-dependent subjects ( N =21) maintained on naltrexone. Subjects completed a 19-day inpatient protocol, which included alcohol abstinence followed by naltrexone treatment (50 mg) on days 15–19. Blood samples were collected after the first administration of naltrexone to evaluate serum levels of naltrexone and 6- β -naltrexol. Regional brain μ -OR binding potential (BP) and δ -OR K i was measured using [ 11 C]carfentanil (CAR) positron emission tomography (PET) and [ 11 C]methyl naltrindole ([ 11 C]MeNTI) PET, respectively, before (day 5) and during naltrexone treatment (day 18). Naltrexone inhibition of [ 11 C]CAR BP was near maximal across all brain regions of interest with little variability across subjects (mean+SD% inhibition=94.9+4.9%). Naltrexone only partially inhibited the [ 11 C]MeNTI K i and there was more variability across subjects (mean+SD% inhibition=21.1+14.49%). Peak serum levels of naltrexone were positively correlated with % inhibition of δ -OR K i in neocortex and basal ganglia. Peak serum levels of naltrexone were not correlated with % inhibition of μ -OR BP. Peak levels of 6- β -naltrexol were not significantly correlated with % inhibition of μ -OR BP or δ -OR K i . Thus, the FDA recommended therapeutic dose of naltrexone was sufficient to produce near complete inhibition of the μ -OR in recently abstinent alcohol dependent subjects. The lower percent inhibition of δ -OR and greater variability in δ -OR blockade by naltrexone across subjects may contribute to individual differences in treatment outcomes to naltrexone. Further investigations on the relationship between individual differences in δ -OR blockade by naltrexone and clinical outcomes should be explored.